2020
DOI: 10.1155/2020/3153891
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Cellular Mechanisms Responsible for Beneficial Effects of Mesenchymal Stem Cell-Derived Product “Exo-d-MAPPS” in Attenuation of Chronic Airway Inflammation

Abstract: Mesenchymal stem cells (MSCs), due to their potential for differentiation into alveolar epithelial cells and their immunosuppressive characteristics, are considered a new therapeutic agent in cell-based therapy of inflammatory lung disorders, including chronic obstructive pulmonary disease (COPD). Since most of the MSC-mediated beneficent effects were the consequence of their paracrine action, herewith, we investigated the effects of a newly designed MSC-derived product “Exosome-derived Multiple Allogeneic Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 63 publications
1
53
0
Order By: Relevance
“…MSC-EVs contain MSC-derived bioactive molecules (microRNAs (miRNAs), enzymes, cytokines, chemokines, and immunomodulatory and growth factors) that generate a tolerogenic phenotype in lung-infiltrated DCs and macrophages which results in enhanced expansion of immunosuppressive Tregs in injured lungs and leads to the alleviation of ongoing inflammation [ 18 , 33 ]. As recently demonstrated by us and others [ 34 , 35 ], in a similar manner as their parental cells, MSC-EVs efficiently attenuated detrimental immune responses in the lungs and promoted enhanced lung repair and regeneration. Reduced expression of costimulatory molecules, downregulated production of Th1- (IL-12, TNF- α , and IFN- γ ) and Th17-inducing cytokines (IL-1, IL-6, and IL-23), and attenuated capacity of antigen-presentation capacity were noticed in DCs and macrophages isolated from the inflamed lungs of MSC-EV-treated animals [ 34 , 35 ].…”
Section: Therapeutic Potential Of Msc-derived Extracellular Vesiclsupporting
confidence: 65%
See 1 more Smart Citation
“…MSC-EVs contain MSC-derived bioactive molecules (microRNAs (miRNAs), enzymes, cytokines, chemokines, and immunomodulatory and growth factors) that generate a tolerogenic phenotype in lung-infiltrated DCs and macrophages which results in enhanced expansion of immunosuppressive Tregs in injured lungs and leads to the alleviation of ongoing inflammation [ 18 , 33 ]. As recently demonstrated by us and others [ 34 , 35 ], in a similar manner as their parental cells, MSC-EVs efficiently attenuated detrimental immune responses in the lungs and promoted enhanced lung repair and regeneration. Reduced expression of costimulatory molecules, downregulated production of Th1- (IL-12, TNF- α , and IFN- γ ) and Th17-inducing cytokines (IL-1, IL-6, and IL-23), and attenuated capacity of antigen-presentation capacity were noticed in DCs and macrophages isolated from the inflamed lungs of MSC-EV-treated animals [ 34 , 35 ].…”
Section: Therapeutic Potential Of Msc-derived Extracellular Vesiclsupporting
confidence: 65%
“…Reduced expression of costimulatory molecules, downregulated production of Th1- (IL-12, TNF- α , and IFN- γ ) and Th17-inducing cytokines (IL-1, IL-6, and IL-23), and attenuated capacity of antigen-presentation capacity were noticed in DCs and macrophages isolated from the inflamed lungs of MSC-EV-treated animals [ 34 , 35 ]. Consequently, significantly lower number of lung-infiltrating, inflammatory, TNF- α - and IFN- γ -producing Th1 cells and IL-17-producing Th17 cells and significantly higher number of immunosuppressive, IL-10- and TGF- β -secreting Tregs were found in MSC-EV-treated mice [ 34 , 35 ].…”
Section: Therapeutic Potential Of Msc-derived Extracellular Vesiclmentioning
confidence: 99%
“…Moreover, the exosomes are capable of affecting the migratory and antigen-presenting properties of DCs, which contribute to the attenuated activation of CD4+ and CD8+ T lymphocytes. Importantly, this study has also demonstrated that inhalation of MSC-exosomes indicate an improved FEV1, PEF, 6-min walking distance (6MWD) and quality of life in COPD patients, with alleviated emphysematous changes, including less hyperexpanded lung, less flattened diaphragms and reduced centrilobular and paraseptal emphysema [94]. In what could be another mechanism for MSC-EVs in COPD, Kim et al have shown that unlike MSC-derived natural exosomes, MSC-derived artificial nanovesicles (3 × 10 7 artificial nanovesicle particles generated from 7 × 10 7 ASCs) display a more efficient regenerative capacity to reduce the mean linear intercept (MLI) primarily through activating the FGF-2 signalling pathway [95].…”
Section: Chronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 58%
“…As the lungs are in direct contact with the external environment, they are prone to different infections including viral diseases. Over the past decade, a considerable number of studies shed light on the therapeutic effects of MSCs for lung diseases, such as ARDS [19] , [20] , [21] , [22] , [23] , chronic obstructive pulmonary disease (COPD) [24] , [25] , [26] , [27] , [28] , Asthma [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , and idiopathic pulmonary fibrosis (IPF) [43] , [44] , [45] , [46] , [47] , [48] .…”
Section: An Overview Of Mscs In Viral Infections; Historical Evidencementioning
confidence: 99%